Hubungan Karakteristik, Beban Kerja dan Motivasi Kerja Perawat Pelaksana dengan Pelaksanaan Standar Prosedur Operasional (SPO) Pemberian Obat Oral di Ruang Rawat Inap RS X Kota Dumai - Azri Yani Nurman; Setyowati Setyowati; Lili Fajria (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Hospital nursing service quality is affected by the workload of nurses in the inpatient room, nurse motivation in carrying out actions oral drug delivery in accordance with standard operating procedures. The purpose of this study to analyze the relationship characteristics, workload and work motivation of nurses to the implementation of standard operating procedures oral drug delivery in inpatient hospital in Dumai. This type of research uses quantitative observational analytic design with cross sectional approach. Samples were 67 nurses in inpatient hospital in Dumai. The results showed no significant relationship between age, education, sex, and length of employment. And there is a significant relationship between workload and work motivation and meaningful implementation between workload and motivation to conduct labor standard operating procedure p value = 0.005 and p value = 0.000 (p <0.05), as well as work motivation is a factor the most dominant in the implementation of standard operating procedures oral drug delivery (OR value = 7.686). It is suggested to hospital management supervision and socialization, employment assessment on the implementation of standard operating procedures oral drug delivery and optimization of workload of nurses in the inpatient hospital in Dumai.